PERAN LABEL HALAL DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH DI KOTA PALEMBANG - Yuni Adinda Putri (Jurnal Bisnis Terapan, 2022)
Abstract The cosmetic product sector in Indonesia is overgrowing. The increasing popularity of halal cosmetics has an impact on increasing the need for cosmetic products. Thus, various manufacturers from various brands offer advantages in terms of quality and benefits and a halal assurance to provide a sense of safety for consumption. This can stimulate purchasing decisions for these products based on these considerations from the various cosmetic products available in the market. Wardah is one cosmetic product company that prioritizes the halal brand image. The sample in this study was 110 samples. Data analysis in this research used the SPSS version 25 program. The halal label has a positive and substantial impact on purchasing decisions. The hypothesis test has an absolute value of 0.030, or lower than 0.05 and a regression coefficient of 0.158 (positive). Brand image has a positive and substantial impact on purchasing decisions. Testing the hypothesis obtained an absolute value of 0.001, or lower than 0.05 and a regression coefficient of -0.341 (negative). The results of this study show that the halal label variable (X1) has a positive and substantial impact on purchasing decisions (Y) for Wardah products in Palembang City.